Personification as Manifestation of Author’s Ironical Attitude from the Title-Text Correlation Standpoint (in the novel Animal Farm by G. Orwell) - Mkhitaryan, Irina (Armenian Folia Anglistika, 2017)
The paper attempts at presenting the author’s ironical attitude in the allegorical novel “Animal farm” written by G. Orwell. Here we posit the idea that the author’s ironical attitude can be embodied by personification, a figure of speech, which makes inanimate objects, animal characters or abstract ideas seem just like people by giving them human traits. The article also clarifies the role of context in defining the title-text correlation, which is best marked by the superiority of pigs ruling the farm instead of people. Hence, the former Manor Farm comes to be named Animal farm, postulating the abilities and strength of animals.
Keywords: irony; personification; context; title-text correlation; modality